Analisis Karya Seni Fotografi Makro sebagai Media Informasi dan Media Pembelajaran - Azzahra, Desya Puteri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
The development in the world of photography is currently experiencing a fairly rapid increase along with the increasingly diverse prices of cameras such as DSLRs that are starting to be affordable. One of the unique fields of photography is Macro Photography, which is a technique of taking photos of small objects with clear details. The role of learning media for educators can be a supporting role in teaching and learning activities. Macro Photography can also be used as one of the learning media used in teaching and learning activities. After conducting research with descriptive qualitative methods, and using analysis that refers to the data obtained, as well as utilizing existing theories as supporting material, the purpose of this research is to find out how the influence of macro photography when used as a learning medium in teaching and learning activities.